Analyzing Policy-Making II : Policy Network Analysis - Kenis, Patrick; Schneider, Volker (My University, 2019)
This chapter introduces network analysis as a method for media policy research. We point to the fact that the use of network analysis implies a specific perspective: the explanation of phenomena in terms of relationships among a system of interdependent actors. We demonstrate that this perspective is by now highly recognized and that it is relevant in all areas where we expect the interdependencies between actors to be more important or complementary to the attribute characteristics of the actors. The chapter gives an overview of the network method by pointing to the type of data which are collected, how they can be presented and visualized and what type of descriptors are helpful in making theoretical and practical sense of the data. We present concepts such as density, centralization and subgraphs and components. The relevance of the method for media policy research is demonstrated by presenting two studies: The introduction of a new electronic medium and Discourse networks in anti-hate speech regulation of Social Media in Germany. Both studies are a good example of the fact that the use of network analysis has produced different and innovative insights.
Keywords: 320